(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
The marine mucilaginous tube-forming benthic diatoms Berkeleya hyalina (Round et Brooks) Cox and Parlibellus berkeleyi (Kütz.) Cox are reported for the fist time for the Caribbean coast of Colombian, in Santa Marta area. These two species were found infrequently growing as macroscopic colonies inhabiting shallow rocky substrata. The report of P. berkeleyi species is the fist for the Caribbean Sea.